ANTI-BULLYING EDUCATION BASED ON SIRAH NABAWIYAH: ANALYSIS OF VALUES IN AR-RAHIQ AL-MAKHTUM AND ITS CONTEXTUALIZATION IN MORAL EDUCATION - Nurwahida; Abdurrahman Getteng; St. Wardah Hanafie Das; Mahsyar Idris (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
This research is motivated by the rampant practice of bullying in the educational environment which shows the weak internalization of moral and spiritual values in the formation of students' character. The purpose of this study is to analyze the values of anti-bullying education in Ar-Rahiq al-Makhtum and contextualize it in the implementation of moral education in Islamic educational institutions. This study uses a qualitative approach with the type of library research through documentation techniques on primary and secondary sources, which are analyzed using content analysis and thematic analysis. The results of the study show that the practice of bullying has occurred since the early days of Islam in the form of verbal, physical, social, and economic violence that is systemic in nature. The prophetic response to bullying is carried out through the internalization of the values of patience, tawakkal, and forgiveness that are preventive and transformative. In addition, the concept of Arkanuddin (faith, Islam, ihsan) serves as an integrative framework in forming non-aggressive behavior. This study concludes that anti-bullying values in Sirah Nabawiyah have conceptual and applicative relevance in modern moral education through an exemplary approach, habituation, and internalization of values